Faktor-Faktor yang Berhubungan fengan Kecemasan Anggota Keluarga terhadap Penularan TB Paru di Wilayah Kerja Puskesmas Sokaraja II Kabupaten Banyumas - Priyatin, Wiwik (Jurnal Keperawatan Soedirman, 2007)
Lungs Tuberculoses is a contagious diseases, so if one of the member in the family got this disease, it will very influence other members of the family. Moreover, it causes the worries feeling to be contagious of this illness. The problem of this research is whatÃ¢â‚¬â„¢s the factors that related to the worries of the familyÃ¢â‚¬â„¢s member in public health of Sokaraja II, in Banyumas Regency through the contagion of lungs tuberculosis. The general aim of this writing is to get the worries, description of the familyÃ¢â‚¬â„¢s member through the lungs TBÃ¢â‚¬â„¢s Contagious diseases in public health of Sokaraja II, in Banyumas regency and the specific aim is to know the relation of gender, age, education, economy condition, occupation, the familyÃ¢â‚¬â„¢s member perception of lungs TB diseases, The FamilyÃ¢â‚¬â„¢s member perception on the contagion of the lungs TB. This research is an analytical descriptive, thatÃ¢â‚¬â„¢s explain the relationship of the variabels through the hypothesis evaluation. The Method of the research that used in this writing is survey method by cross sectional approach. It is an approach that done by the time the decided or chosen by the writer with some variabels in one time. The Samples of this research is questionnaire. Data analysis that used in this research is descriptive analysis, itÃ¢â‚¬â„¢s the percentages to know the characteristics of the respondents. Ã¢â‚¬Å“chi squere and product momentÃ¢â‚¬Â to know the factors that related with the lungs TB contagiousÃ¢â‚¬â„¢ worries of the familyÃ¢â‚¬â„¢s member. The result of the research shows that the gender, ages, education, economy condition, occupation, the familyÃ¢â‚¬â„¢s perception of the lungs TB illness and the perception through the treatment of lungs TB has a significant relationship with the familyÃ¢â‚¬â„¢s member worries through the lungs TB Contagion.